2009
DOI: 10.1080/00949650802174397
|View full text |Cite
|
Sign up to set email alerts
|

A mean deviation-based approach to monitor process variability

Abstract: The study proposes a Shewhart-type control chart, namely an MD chart, based on average absolute deviations taken from the median, for monitoring changes (especially moderate and large changes -a major concern of Shewhart control charts) in process dispersion assuming normality of the quality characteristic to be monitored. The design structure of the proposed MD chart is developed and its comparison is made with those of two well-known dispersion control charts, namely the R and S charts. Using power curves as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Since it is difficult to obtain E(MD) analytically, it is obtained by simulation. Extensive tables for t 2 (n) can be found in Riaz and Saghir (2009). The advantage of this estimator is that it is less sensitive to outliers than R (cf.…”
Section: Estimators Of the Standard Deviationmentioning
confidence: 99%
“…Since it is difficult to obtain E(MD) analytically, it is obtained by simulation. Extensive tables for t 2 (n) can be found in Riaz and Saghir (2009). The advantage of this estimator is that it is less sensitive to outliers than R (cf.…”
Section: Estimators Of the Standard Deviationmentioning
confidence: 99%
“…Recently, Riaz and Saghir [26] proposed a Shewhart-type dispersion control chart based on the MD which they named the MD chart. They showed that the MD chart is superior to both R and S charts in terms of its power for detecting shifts in process variability.…”
Section: Introductionmentioning
confidence: 99%
“…Because it is di cult to obtain the constant t 2 (n) analytically, it has to be obtained by simulation. Extensive tables of t 2 (n) can be found in Riaz and Saghir (2009). Like G, we can rewrite ADM as a function of order statistics.…”
Section: Estimators Of the Standard Deviationmentioning
confidence: 99%